Buku Fotografi Tari Piring Maestro Syofyani - Jasmin, Mega; Kurniawan, Ivan (Fakultas Desain Universitas Komputer Indonesia, 2022)
Globalization is an acceleration that affects life. The current of globalization brings society to a universal culture. Universal culture is all cultural civilizations that exist on earth. The problem found is that universal culture can erode traditional culture as well as the lack of information on the theme of Tari Piring. The object of design in this final report is Tari Piring and teenager who are currently studying high school. The solution to solving this problem is to document local wisdom regarding the importance of undocumented intellectual work assets. You do this by using book media as a window to knowledge. Thus, teenager can get knowledge information about West Sumatra Plate Dance and can pass it on to the next generation of the nation.